Corrosion performance of 5182 aluminium alloy in calcium chloride solution. (2016) - Cui, Y.; Xu, W.; Du, M.; Han, Q.
Corrosion behaviour of 5182 aluminium was evaluated in terms of weight change in a 30% calcium chloride solution at temperatures ranging from 0°C to 65°C. The test results indicate that there is a critical temperature (35°C) above which the alloy experiences weight gain and below which the alloy experiences weight loss during the corrosion processes. Optical light microscopy (OLM), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) were carried out to characterise the corrosion behaviour of this alloy. The results indicate that weight gain and weight loss occur under different corrosion mechanisms.